Surgical factors affecting regionally metastatic cutaneous squamous cell carcinoma to the parotid gland. Issue 5 (8th March 2023) - Rao, Vishwanatha M.; Feng, Allen L.; Deschler, Daniel G.; Kaufman, Howard L.; Lin, Derrick T.; Miller, David; Richmon, Jeremy D.; Shalhout, Sophia Z.; Varvares, Mark A.; Emerick, Kevin S.
Abstract: Background: Understanding the impact of surgical treatment on regionally metastatic cutaneous squamous cell carcinoma (cSCC). Methods: Retrospective series of 145 patients undergoing parotidectomy and neck dissection for regionally metastatic cSCC to the parotid. Overall survival (OS), disease‐specific survival (DSS), and disease‐free survival (DFS) analyzed over 3 years. Multivariate analysis was completed using Cox proportional hazard models. Results: OS was 74.5%, DSS was 85.5% and DFS was 64.8%. On multivariate analysis, immune status (HR = 3.225[OS], 5.119[DSS], 2.071[DFS]) and lymphovascular invasion (HR = 2.380[OS], 5.237[DSS], 2.595[DFS]) were predictive for OS, DSS, and DFS. Margin status (HR = 2.296[OS], 2.499[DSS]) and ≥18 resected nodes (HR = 0.242[OS], 0.255[DSS]) were predictive of OS and DSS, while adjuvant therapy was predictive of DSS ( p = 0.018). Conclusions: Immunosuppression and lymphovascular invasion portended worse outcomes in patients with metastatic cSCC to the parotid. Microscopically positive margins and <18 nodes resected are associated with worse OS and DSS, while patients receiving adjuvant therapy had improved DSS.